INVESTMENT OPPORTUNITY SET DAN FREE CASH FLOW PADA TINGKAT PEMBAYARAN DIVIDEN PERUSAHAAN MANUFAKTUR - Aristantia, Dwi; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 11 No 1 (2015), 2015)
The purpose of this research was to examine the effect of investment opportunity sets and free cash flow to level of dividend payments of manufacturing companies recorded in the Indonesia Stock Exchange from 2009 to 2013. This needs to be investigated because of the fluctuations in the level of dividend payments on manufacturing companies in that period. Total of 30 companies sampled in this study were obtained through purposive sampling method in accordance with certain criteria. The results of this research showed that investment opportunity set doesn’t influence level of dividend payments and free cash flow have positive effect to level of dividend payments. Both of these variables simultaneously affect the level of dividend payments. 17,9 percent change in the level of dividend payments in manufacture companies can be explained by the variables investment opportunity set and free
Keywords: free cash flow, investment opportunity set, level of dividend payments